Pregnancy after bariatic surgery and the risk of pre‐eclampsia. (8th November 2021) - Devlieger, R; Ceulemans, D
Abstract : Linked article: This is a mini commentary on K Johansson et al., pp. 461–471 in this issue. To view this article visit https://doi.org/10.1111/1471-0528.16871